IMPACT OF DEMONETISATION ON SMALL SCALE INDUSTRIES IN KANYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The main aim of the study is to study the impact on demonetization on production and sale of product, the impact of demonetization on the employment and the reasons for demonetization among the SSI entrepreneurs. For achieving the objective of this study and to conduct the investigation, data have been collected from both the primary as well as the secondary sources of data collection both methods were use to get appropriate result and more accurate conclusion